SISTEM OPERASIONAL LEMBAGA KEUANGAN SYARIAH DAN KONTRIBUSINYA TERHADAP PEMBERDAYAAN UMAT - Sindy Wahyu Silvia; Eko Arief Cahyono; Indri Putri Pratiwi (EKSYA : Jurnal Ekonomi Syariah, 2025)
This article examines the implementation of the operational systems of Islamic Financial Institutions (LKS) and their contribution to enhancing community empowerment. LKS represents an alternative financial system based on Sharia principles, including the prohibition of usury (riba), uncertainty (gharar), and speculation (maisir). This study employs a qualitative approach, utilizing a literature review method to analyze various scholarly sources and official documents. The findings indicate that LKS carries out fund collection and distribution through Sharia-compliant contract schemes such as mudharabah, musyarakah, murabahah, ijarah, salam. These operations are supervised by the Sharia Supervisory Board (DPS), the Financial Services Authority (OJK), and the National Sharia Council – Indonesian Ulema Council (DSN-MUI) to ensure full compliance with Islamic principles. Furthermore, LKS integrates Sharia-based financial technology (fintech) to promote inclusive financial services and innovation. From a social perspective, LKS plays a significant role in supporting micro, small, and medium enterprises (MSMEs), providing Sharia-compliant financing, managing Islamic social funds—such as zakat, infak, sedekah, and waqf—productively, and enhancing public awareness of Islamic financeThese findings confirm that LKS serves not only as a financial intermediary but also as a catalyst for community empowerment, contributing to the development of a just and sustainable economic system.